Efficient protein depletion by genetically controlled deprotection of a dormant N-degron: report - Taxis, Christof; Stier, Gunter; Knop, Michael (Molecular systems biology, 2009)
Methods that allow for the manipulation of genes or their products have been highly fruitful for biomedical research. Here, we describe a method that allows the control of protein abundance by a genetically encoded regulatory system. We developed a dormant N-degron that can be attached to the N-terminus of a protein of interest. Upon expression of a site-specific protease, the dormant N-degron becomes deprotected. The N-degron then targets itself and the attached protein for rapid proteasomal degradation through the N-end rule pathway. We use an optimized tobacco etch virus (TEV) protease variant combined with selective target binding to achieve complete and rapid deprotection of the N-degron-tagged proteins. This method, termed TEV protease induced protein inactivation (TIPI) of TIPI-degron (TDeg) modified target proteins is fast, reversible, and applicable to a broad range of proteins. TIPI of yeast proteins essential for vegetative growth causes phenotypes that are close to deletion mutants. The features of the TIPI system make it a versatile tool to study protein function in eukaryotes and to create new modules for synthetic or systems biology.
Gesehen am 14.08.2017